2010
DOI: 10.1097/hjh.0b013e3283362762
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of the antihypertensive effects of music-guided slow breathing

Abstract: Background The possibility that daily sessions of musicguided slow breathing may reduce 24-h ambulatory blood pressure (ABP), and predictors of efficacy were explored in a randomized, placebo-controlled trial with parallel design.Methods Age-matched and sex-matched hypertensive patients were randomized to music-guided slow breathing exercises (4-6 breaths/min; 1 : 2 ratio of inspiration : expiration duration) (Intervention; n U 29) or to control groups who were thought to relax while either listening to slow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
3
20
1
Order By: Relevance
“…e results of this study showed that SBP and DBP decreased in the TG group, which is consistent with the results of Modesti [50].…”
Section: Discussionsupporting
confidence: 91%
“…e results of this study showed that SBP and DBP decreased in the TG group, which is consistent with the results of Modesti [50].…”
Section: Discussionsupporting
confidence: 91%
“…The effects detected are similar in magnitude to those observed with other methods capable of inducing a relaxation response, such as music-guided slow breathing [Grossman 2001;Modesti 2010].…”
Section: Discussionsupporting
confidence: 74%
“…Slow breathing exercises have been reported to improve vagal tone and decrease sympathetic tone [30, 31], especially in prehypertensives [32]. Moreover, prior studies by Parati et al have demonstrated antihypertensive effects of music-guided slow breathing exercises [33, 34]. Therefore, it is proposed that the offspring of hypertensive parents should regularly practice these breathing exercise programs and maintain their sympathovagal homeostasis to prevent the development of prehypertension.…”
Section: Discussionmentioning
confidence: 99%